Cassie the caterpillar - Johnson, Rebecca, 1966- (Glebe, NSW : Pascal Press, 2013)
Through engaging images and a witty story, this Cassie the Caterpillar story book teaches children about the needs and environments of the caterpillar.
"A Steve Parish kids story book"
"Reading level 18"--Cover verso.
For primary school age.
Keywords: Caterpillars -- Juvenile literature; Caterpillars -- Australia -- Juvenile literature; Insects -- Juvenile literature; Australian